2000
DOI: 10.1002/1097-0142(20000815)89:4<863::aid-cncr19>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Is thyroidectomy necessary in RET mutations carriers of the familial medullary thyroid carcinoma syndrome?

Abstract: BACKGROUND The results and consequences of genetic testing in a family with familial medullary thyroid carcinoma (FMTC) are described. METHODS In the screening of relatives, serum calcitonin is replaced by RET mutation analysis that was performed in families suspected of hereditary medullary thyroid carcinoma (MTC). In 4 of 10 families, mutation in exon 10 was found in codon 611. RESULTS One hundred fifty persons belonging to 30 families were tested, of which 10 families were carriers of RET mutation in exon 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Considering our data, many of the germline mutations running in German RET families obviously were created by spontaneous mutation many decades, if not centuries ago. In keeping, rare literature reports ( Table 1) [12][13][14][15][16][17][18][19][20] suggested that the germline mutation in some RET families can be fairly old, existing since 1896 at the latest in a Swedish RET family harbouring the C618S mutation, 15 and possibly since 1865 at least in a German RET family with the C634W mutation. 20 Rigorous ascertainment of RET carriers with solitary, seemingly sporadic tumours, early family screening, early surgical intervention, and continual hormonal and radiological surveillance, in all likelihood, minimize differential effects that detection bias otherwise might have had on the identification of carriers with different RET mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering our data, many of the germline mutations running in German RET families obviously were created by spontaneous mutation many decades, if not centuries ago. In keeping, rare literature reports ( Table 1) [12][13][14][15][16][17][18][19][20] suggested that the germline mutation in some RET families can be fairly old, existing since 1896 at the latest in a Swedish RET family harbouring the C618S mutation, 15 and possibly since 1865 at least in a German RET family with the C634W mutation. 20 Rigorous ascertainment of RET carriers with solitary, seemingly sporadic tumours, early family screening, early surgical intervention, and continual hormonal and radiological surveillance, in all likelihood, minimize differential effects that detection bias otherwise might have had on the identification of carriers with different RET mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was made concomitantly to MTC in one case (25 years of age) and 9, 12, and 15 years after the thyroid tumor (26,30, and 31 years of age).…”
Section: Pheo and Hptmentioning
confidence: 99%
“…Theoretically, if thyroid surgery is performed before the neoplastic transformation from C-cell hyperplasia to MTC, the prophylactic procedure can be limited to the thyroid gland. When performed by an experienced endocrine surgeon, this intervention presents few complications and a high rate of biochemical cure (18)(19)(20)(21)(22)(23)(24)(25)(26). Indeed, recent studies evaluating the follow-up of children who underwent total thyroidectomy prophylactically have reported a lower incidence of persistent or recurrent disease (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…All three patients could have acquired additional, albeit unrecognized, germline or somatic mutations. Variation in expression and penetrance has been described for RET codons 611, 618, 790, 791 and 804 [12, 41–44]. These examples epitomize how unreliable individual predictions of phenotype can be when these are based solely on RET genotype.…”
Section: Genotype–phenotype Correlations Of Age‐related Progressionmentioning
confidence: 99%